2022
DOI: 10.1109/access.2022.3147838
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Wheat Unsound Kernels Based on Improved ResNet

Abstract: In the process of grain acquisition, the unsound kernel of wheat is detected mainly by manual detection, and the method of detection by computer vision is still in the experimental stage. Aiming at the problems such as expensive equipment for image acquisition, difficulty in adhesion segmentation, and low recognition efficiency in detection, this paper takes six kinds of wheat as objects, namely sound kernel, broken kernel, sprouted kernel, injured kernel, moldy kernel and spotted kernel, builds a wheat image … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Moreover, we confirmed that the CNN model is more accurate than the latest DenseNet model. Because the DenseNet model tends to extract similar features as the hierarchy deepens, which affects accuracy [52]. Our study shows that the CNN model is better than the DenseNet model in terms of the classification accuracy.…”
Section: B Classification Accuracies Obtained From M-densenet and C-d...mentioning
confidence: 84%
“…Moreover, we confirmed that the CNN model is more accurate than the latest DenseNet model. Because the DenseNet model tends to extract similar features as the hierarchy deepens, which affects accuracy [52]. Our study shows that the CNN model is better than the DenseNet model in terms of the classification accuracy.…”
Section: B Classification Accuracies Obtained From M-densenet and C-d...mentioning
confidence: 84%
“…In conclusion, researchers at home and abroad have undertaken a series of studies on the detection of agricultural products and achieved good results [18][19][20][21], which provided a reference for the detection of maize kernel quality. For example, Bi et al [22] combined deep learning with machine vision and used the basis of Swin Transformer to improve maize seed recognition.…”
Section: Introductionmentioning
confidence: 99%
“…At present, deep learning has been widely applied in agriculture. Convolutional neural network technology has been applied in the actual agricultural environment, such as image classification [26][27][28], object detection [29][30][31][32], and image segmentation [33][34][35][36][37], with good performance. Therefore, the study of peanut kernels and peanut pods in this field has attracted the attention of many scholars.…”
Section: Introductionmentioning
confidence: 99%